Takhlil al-Akhta' fi al-Kitabah - Akmansyah, Muhammad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2015)
Writingcompetenceis one of four language competences: listening, speaking, reading, and writing. Writingcompetencecoversthree main areas: imla’/dictation, khath/ calligraphy, andta’bir. Arabic languageis known forits uniqueness in pronunciation--which is oftenmisspelled in speaking or errorsinimla’/dictation—nahwu,sharaf, anduslub/structure. Writing errorsoftenoccurs inaspects ofdictation: writing hamzahwashalandhamzahqata', layinghamzah in word. Aspects of nahwu-sharafanddalalah/uslub/structure: writingta’rifandtankir, mudzakarandmuannats, uslub/structure